Year 2010

The working in the bracket should be done first then do the power.

the (1/4-1/8) should be worked out before using the power of two as the answer might vary

instead of 2/3 x [ (1/4)^2 - (1/8)^2 ], it should be 2/3 x [ (1/8)^2 ]we are suppose to do the minusing before the multiplying as the minusing is inside the bracket. so,2/3 x {1/4 - 1/8) = 2/3 x (1/8^2) = 2/3 x 1/4=1/6

It should be 2/3 x (1/4 - 1/8)^2=2/3 x (2/8 - 1/8)^2=2/3 x 1/8^2=2/3 x (1/8 x 1/8)=2/3 x 1/64=1/96

we should solve this first:= 2/3 x (1/4 - 1/8)^2= 2/3 x 1/8^2= 2/3 x 1/64= 1/96

we should do 1/4 - 1/8 first before doing to the power of 2.

Instead of...2／3 x (1/4 - 1/8)^2=2/3 x ( (1/4)^2 - (1/8)^2 )...It should be...2/3 x (1/4-1/8)^2=2/3 x (1/8)^2...

The working in the bracket should be done first then do the power.

ReplyDeletethe (1/4-1/8) should be worked out before using the power of two as the answer might vary

ReplyDeleteinstead of 2/3 x [ (1/4)^2 - (1/8)^2 ], it should be 2/3 x [ (1/8)^2 ]

ReplyDeletewe are suppose to do the minusing before the multiplying as the minusing is inside the bracket. so,

2/3 x {1/4 - 1/8)

= 2/3 x (1/8^2)

= 2/3 x 1/4

=1/6

It should be 2/3 x (1/4 - 1/8)^2

ReplyDelete=2/3 x (2/8 - 1/8)^2

=2/3 x 1/8^2

=2/3 x (1/8 x 1/8)

=2/3 x 1/64

=1/96

we should solve this first:

ReplyDelete= 2/3 x (1/4 - 1/8)^2

= 2/3 x 1/8^2

= 2/3 x 1/64

= 1/96

we should do 1/4 - 1/8 first before doing to the power of 2.

ReplyDeleteInstead of...

ReplyDelete2／3 x (1/4 - 1/8)^2

=2/3 x ( (1/4)^2 - (1/8)^2 )

...

It should be...

2/3 x (1/4-1/8)^2

=2/3 x (1/8)^2

...